Upper respiratory tract infections and influenza-like illnesses among healthcare workers: are serological tests useful in monitoring influenza and influenza-like illness? - Katarzyna Toczek-Kubicka; Filip Szenborn; Ernest Piotr Kuchar; Leszek Szenborn (Nofer Institute of Occupational Medicine, 2022)
Background Healthcare workers (HCWs) are at high risk for exposure to upper respiratory tract infections (URTIs) and influenza-like illnesses (ILIs). The present study aimed to surveil URTIs and ILIs and their impact among the Department of Pediatric Infectious Diseases in Wroclaw employees and evaluate their humoral response to influenza. Material and Methods Thirty-six HCWs participated in the first season and 32 HCWs in the second season during years of the study. The authors carried out a URTI/ILI surveillance, and all HCWs were asked to complete a weekly report during 2 influenza seasons: 2016/2017 (S1) and 2017/2018 (S2). In S1 both IgG and IgM antibodies against influenza A and B were assessed. The HCWs with symptoms of ILI were encouraged to undergo PCR tests for influenza. Results No significant differences in reporting URTI were found among vaccinated and non-vaccinated HCWs and HCWs and the control group. Depending on the year 5.5-17.2% of HCWs were treated with antibiotics because of URTI. In the study 58.7% of participants in S1 and 66.7% in S2 decide to work despite the URTI symptoms. There was no statistical relationship between the concentration of anti-influenza IgG and the number of URTIs and ILIs reported. Only vaccinated were willing to undergo voluntary influenza testing. Conclusions The URTI and ILI occur commonly in HCWs, and HCWs contract URTIs as often as the control group. Despite their medical education, HCWs work with the symptoms of infection and overuse antibiotics to treat the URTI. Serology testing is not able to follow the infection's dynamics or identify the people immune to the influenza-like illness. The diagnostic value of IgM antibodies in acute influenza infection is negligible. Vaccinated HCWs are more focused on their health and are more willing to undergo influenza tests. Med Pr. 2022;73(6):441-7